Artificial chiral nanochannels. Issue 6 (3rd June 2021) - He, Qiang; Tao, Mingjie; Ali, Wajahat; Min, Xuehong; Zhao, Yanxi
ABSTRACT: The biological channels with chiral features are capable of intelligently regulating substance transport through cell membrane, which plays a pivotal role in maintaining normal functions for living organisms. However, the high complexity and variability of biological nanochannels are the major constraints on practical studies. At present, artificial solid-state channels have been developed to simulate the functionality of biological channels. The functional groups are often introduced into nanochannels to achieve selective sensing and transport molecules. In particular, the fast-paced progress has been made in developing artificial chiral nanochannels. This review highlights the recent advancement of artificial chiral nanochannels as constructed using various strategies, including chiral macrocyclic hosts, amino acids, and label-free methods, which are expected to support the researchers working in fields such as supramolecular chemistry, chiral chemistry, and drug development. Graphical Abstract: uf0001